FAKTOR-FAKTOR YANG BERPENGARUH UNTUK MEMPREDIKSI TINGKAT KELULUSAN MAHASISWA MENGGUNAKAN ALGORITMA C4.5 - Wulandari, Dewi Arianti; Bedi, Herman; Luqman, Luqman; Mashuda, Ahmad Arfan (IDEALIS : InDonEsiA journaL Information System, 2024)
Factors that influence student graduation to complete studies at university include academic grades, activeness in organizations, school origin, motivation, and busyness in work. This study aims to determine the factors that influence student graduation rates. Based on the calculation results using the C4.5 algorithm, it turns out that the cumulative achievement index (GPA) factor, high school origin, active organization, active student activity unit (UKM), already working and motivation affect student graduation rates both on-time and not. Based on testing using a confusion matrix, accuracy results of more than 70% were obtained, which means that with the C4.5 algorithm, the resulting model can predict well whether students can graduate on time or not with these factors